School Closures and Returning to School: Views of Parents of Children With Disabilities in England During the Covid-19 Pandemic - Castro-Kemp, Susana; Mahmud, Arif (Frontiers in Education, 2021)
Children and young people with special educational needs and disabilities and their families are likely to be significantly affected by the Covid-19 pandemic at various levels, particularly given the implementation of school closures during national lockdowns. This study employed a survey design to assess parental perspectives on the impact of school closures and of returning to school in England, as a result of the Covid-19 pandemic. Eighty-three parents of children and young people with various types of need responded to the survey between September and December 2020. The survey included multiple choice questions and open-ended questions for further in-depth examination of parental perspectives. Results show that: the majority of parents reported that school closures had a detrimental effect on their children’s mental health (particularly those from the most deprived neighbourhoods) and on their own mental and physical health (particularly for ethnically diverse parents and for those whose children attend specialized settings); returning to school was considered to have a positive impact on children’s mental and physical health for the vast majority of parents, despite fearing exposure to the virus; many parents have reported that their children were calmer and happier at home during school closures and became more anxious and stressed upon returning to school. The role of cumulative risk in these children and families, as well as the role of schools as key support agents for the most vulnerable are discussed with implications for future research and policy.